Antioxidant Activities and Electrochemical Behaviors of Xanthones from Cratoxylum cochinchinense and Cratoxylum formasum - Chailap, Benjamat; Nuanyai, Thanesuan (Naresuan University Journal: Science and Technology (NUJST), 2019)
Seven xanthones; dulcisxanthone B ( 1 ), ß-mangostin ( 2 ), 1,3,7-trihydroxy-2,4-di-(3-methylbut-2-eyl)-xanthone ( 3 ), cudratricusxanthone E ( 4 ), cochinchinone A ( 5 ), 2-geranyl-1,3,7-trihydroxy-4-(3,3-dimethylallyl)-xanthone ( 6 ), and cochinchinone B ( 7 ) were isolated from twigs of Cratoxylum cochinchinense and Cratoxylum formasum . The structures of all isolated compounds were elucidated by spectroscopic methods ( 1 H, 13 C, 1 H- 1 H COSY, 1 H- 13 C HSQC, and 1 H- 13 C HMBC) and compared with previous literatures. All compounds were evaluated in vitro for antioxidant activity using DPPH assay. Their electrochemical behaviors were investigated by cyclic voltammetry. The results derived from two techniques were consistent. Compounds 1 , 2 , 4 and 7 exhibited strong antioxidant activities. Considering the structure-activity relationship, the hydroxy group at C-6 played an important role to antioxidant power. Keywords: Xanthone, Cratoxylum cochinchinense , Cratoxylum formasum , Antioxidant, Electrochemical